A Project feasibility study expansion of Anber Enterprises - Bayron, Eric E.; Otico, Edward P.; Tiu, Benedict G. (Diliman, Quezon City College of Engineering, 1993)
This project feasibility study presents the possibilities of expansion of the production capacity of Anber Enterprises. The objectives of the study are: a. Determine the possibilities of expansion of the production facility through market, technical and financial analyses, b. Prepare a plan detailing the expansion of the system capacity, and c. Determine the impact of the project upon implementation through the social profitability analysis. The plan for expansion covered three possibilities: a. improvement of the current facility, b. acquisition of an additional production facility, and c. transfer to an entirely new facility. The consideration of these was limited by the following factors: a. the company has just entered the direct export market. It has no long history of dealing with the current demand; b. the company has limited financial capability for expansion. By the end of the 1993, the estimated cash balance of the company is less than one million pesos. Results of the market study showed that the demand for Anber's product will be stable and there is an excellent potential for growth. Christmas items, to which these products belong, are experiencing a phenomenal growth with sales reaching 1.4 billion pesos in 1991. With this reason, Anber can consider the expansion of the production capacity a possibility.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Anber Enterprises; Wrought-iron furniture; Participatory monitoring and evaluation (Project management)